A Genomic and Transcriptomic Overview of MATE, ABC, and MFS Transporters in Citrus sinensis Interaction with Xanthomonas citri subsp. citri - Juliao, Maria H. M. [UNESP]; Silva, Saura R. [UNESP]; Ferro, Jesus A. [UNESP]; Varani, Alessandro M. [UNESP] (Mdpi, 2020)
The multi-antimicrobial extrusion (MATE), ATP-binding cassette (ABC), and major facilitator superfamily (MFS) are the main plant transporters families, playing an essential role in the membrane-trafficking network and plant-defense mechanism. The citrus canker type A (CC), is a devastating disease caused byXanthomonas citrisubsp.citri(Xac), affecting all citrus species. In this work, we performed an in silico analysis of genes and transcripts from MATE, ABC, and MFS families to infer the role of membrane transporters in Citrus-Xac interaction. Using as reference, the availableCitrus sinensisgenome and the citrus reference transcriptome from CitrusKB database, 67 MATE, 91 MFS, and 143 ABC genes and 82 MATE, 139 MFS, and 226 ABC transcripts were identified and classified into subfamilies. Duplications, alternative-splicing, and potentially non-transcribed transporters' genes were revealed. Interestingly, MATE I and ABC G subfamilies appear differently regulated during Xac infection. Furthermore,Citrusspp. showing distinct levels of CC susceptibility exhibited different sets of transporters transcripts, supporting dissimilar molecular patterns of membrane transporters in Citrus-Xac interaction. According to our findings, 4 MATE, 10 ABC, and 3 MFS are potentially related to plant-defense mechanisms. Overall, this work provides an extensive analysis of MATE, ABC, and MFS transporters' in Citrus-Xac interaction, bringing new insights on membrane transporters in plant-pathogen interactions.
Keywords: citrus canker; comparative genomics; membrane transporters; differentially expressed genes; plant-pathogen interactions